2006
DOI: 10.1111/j.1365-2656.2006.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal mass and condition on energy transfer in Weddell seals

Abstract: Summary1. Environmental variation influences food abundance and availability, which is reflected in the reproductive success of top predators. We examined maternal expenditure, offspring mass and condition for Weddell seals in 2 years when individuals exhibited marked differences in these traits. 2. For females weighing ≥ 355 kg there was a positive relationship between maternal post-partum mass (MPPM) and lactation length, but below this there was no relationship, suggesting that heavier females were able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
162
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(170 citation statements)
references
References 62 publications
6
162
0
2
Order By: Relevance
“…Phocid seals derive the majority of energy for lactation from maternal body stores (see Wheatley et al 2006). Thus there is potential to physiologically assess the probability of achieving viable weaning mass for each pup, during pregnancy, on the basis of maternal nutritional state (Trites & Donnelly 2003).…”
Section: Life History Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Phocid seals derive the majority of energy for lactation from maternal body stores (see Wheatley et al 2006). Thus there is potential to physiologically assess the probability of achieving viable weaning mass for each pup, during pregnancy, on the basis of maternal nutritional state (Trites & Donnelly 2003).…”
Section: Life History Strategymentioning
confidence: 99%
“…However, we suggest that Weddell seal investment is more prudent than simply randomly sampling a variable environment. Based on temporal variability in reproductive rate, combined with lack of evidence for costs of reproduction, we infer that Weddell seals prudently select years for reproduction, pre-empting challenging reproductive attempts.Phocid seals derive the majority of energy for lactation from maternal body stores (see Wheatley et al 2006). Thus there is potential to physiologically assess the probability of achieving viable weaning mass for each pup, during pregnancy, on the basis of maternal nutritional state (Trites & Donnelly 2003).…”
mentioning
confidence: 99%
“…This study shows that despite the seasonal changes in Weddell seal activity budgets (Kooyman 1975;Castellini et al 1992a;Schreer and Testa 1996;Forcada et al 2012) and body condition (Wheatley et al 2006;Shero et al 2015), their ability to sustain aerobic metabolism while underwater as indicated by TBO 2 stores is conserved across the winter. Variation in O 2 stores was most strongly correlated with animal mass, and not season.…”
Section: Discussionmentioning
confidence: 99%
“…This comparison accounting for animal body composition is most physiologically relevant, as it tests whether there are differences in O 2 -storage capacities in the lean body compartment. Weddell seals exhibited a relatively small over winter increase in body condition (lipid increased by 6 %TBM) as compared to other marine mammal species and at different times of the year (i.e., lipid may decrease by 15 %TBM across lactation; Costa et al 1986;Beck et al 2003;Wheatley et al 2006;Crocker et al 2014). Still, these small changes in lipid stores were enough to bias interpretations of seasonal differences in TBO 2 stores, before including body composition in statistical models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation